Sizing software for residential grid-connected photovoltaic system - Abdul Rasid, Nurul Afiqa (2013)
This final year project report presents software for sizing residential Grid-Connected Photovoltaic Systems developed by Microsoft Visual Basic. The software represents two design goals which are to meet specific output energy from the system and to maximize energy output from available roof space. The sizing process involves the selection of PV modules and inverter and computation of technical performance and expected income of the system. As existing sizing software for photovoltaic system such as PVSyst required manual selection of PV modules configuration and estimated PV array capacity (kWp), this sizing software perform automatic selection of PV modules and estimated PV array capacity.